The Influence of Work Motivation and Discipline on Employee Performance at PT. PLN (Persero) UP3 North Makassar - Luthfiana, Andi Gita Aqilah; Nurman; Dipoatmodjo, Tenri S.P.; Natsir, Uhud Darmawan; Burhanuddin (International Humanity Advance, Business & Sciences, 2024)
This study examines the Effect of Work Motivation and Discipline on Employee Performance at PT. PLN (Persero) UP3 North Makassar. The purpose of this study was to determine the effect of work motivation and discipline on employee performance at PT. PLN (Persero) UP3 North Makassar. The data collection was carried out by distributing questionnaires with a total sample of 64 respondents and using a quantitative descriptive approach. Therefore, the data analysis used is statistical analysis in the form of multiple linear regression tests. The results of this study indicate that partially and simultaneously the variables of motivation and discipline have a positive effect on the performance of PT. PLN (Persero) UP3 North Makassar. This is evidenced by the results of the Simultaneous Test (F Test) and the results of the Partial Test (t test) which also show the significant values ​​of the two independent variables that support the hypothesis. Therefore the test results of this study state that there is a simultaneous influence between the variables of motivation and work discipline on the performance of PT. PLN (Persero) UP3 North Makassar.